Management Of Non-performing Loans In Banking Institution-study Case Badr- - Meziane, Imene; Berrazouane, Hassan (جامعة الوادي - University of Eloued, 2023)
The study aimed to determine the impact of non-performing loans on the granting of loans, highlighting the various theoretical concepts of non-performing loans and how to manage them in the banking institution, as well as the various methods and mechanisms for the collection and recovery of non-performing loans in the Bank of Agriculture and Rural Development. The study concluded that the disruption of loans is the result of various reasons that may be due to the borrower himself or the financial institution or for sudden reasons outside of all parties and The methods of processing the loan vary according to the reasons that lead to it
مقال
Keywords: loans ; distressed loans ; Banks ; non-performing loans ; Loan Processing